2016
DOI: 10.1002/er.3565
|View full text |Cite
|
Sign up to set email alerts
|

Steam co-gasification of iron-loaded biochar and low-rank coal

Abstract: SUMMARYSteam co-gasification of iron catalyst-loaded biochar, which was produced by the pyrolysis of woody biomass and Indonesian Adaro subbituminous coal at 800°C, was carried out in this study. The main purpose of this work was to examine the effectiveness of an iron catalyst loaded on biochar for hydrogen (H 2 ) evolution. It was shown that the H 2 evolution for a mixed sample of iron-loaded biochar (20 wt%) and Indonesian Adaro subbituminous coal increased by 20% compared with that for the coal sample with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The particle size, the proximate, and the ultimate analyses were identical to our previous studies [17] as shown in Tables 1 and 2. The iron species was a commercial Fe 2 O 3 (α-Fe 2 O 3 ).…”
Section: Experimental Samplessupporting
confidence: 53%
See 4 more Smart Citations
“…The particle size, the proximate, and the ultimate analyses were identical to our previous studies [17] as shown in Tables 1 and 2. The iron species was a commercial Fe 2 O 3 (α-Fe 2 O 3 ).…”
Section: Experimental Samplessupporting
confidence: 53%
“…The form of iron catalyst after pyrolysis and steam gasification was measured by XRD under conditions that were identical to what was previously reported [17].…”
Section: Characterization Of the Pyrolyzed Char And Gasified Residuementioning
confidence: 85%
See 3 more Smart Citations